Health Services Use Among Veterans Using U.S. Department of Veterans Affairs and Mainstream Homeless Services. Issue 4 (December 2013) - Byrne, Thomas; Montgomery, Ann Elizabeth; Treglia, Daniel; Roberts, Christopher Brent; Culhane, Dennis P.
<x xml:space="preserve">Abstract</x> We examined the use of health and behavioral health services for two groups of homeless veterans (N = 1, 302) in the New York City area who were enrolled in the U.S. Department of Veterans Affairs (VA) healthcare system—veterans who use VA homeless programs, and veterans who use mainstream homeless programs only. Using administrative records from the VA and the New York City Department of Homeless Services, we compared the characteristics of users of VA and mainstream homeless programs and examined between‐group differences in VA inpatient and outpatient services use and within‐group changes in services use prior and subsequent to onset of homelessness. Roughly 41 percent of veterans only used mainstream homeless services. There were no significant differences between users of VA and mainstream homeless services in terms of gender, age, ethnicity, and level of VA eligibility. Veterans who used only mainstream homeless assistance services were less likely to be engaged with—and made less intensive use of—VA health and behavioral health inpatient and outpatient services than those who used VA homeless services. Efforts should be made to identify and engage veterans who, while enrolled in VA healthcare, may go unidentified as homeless by the VA.